Mediatic visibilities and invisibilities (RuMoRes, 2014)
The present edition of Rumores, online Magazine on Communication, Language and Media, corresponding to the number 15, first semester of 2014, focuses on the subject of invisibility in the media. Two main questions are posed: how can such subject be approached theoretically and who are the characters to embody the stories. In that sense, we have the honor to publish the thematic dossier "The visibility of the unknown", resulting from the homonimous seminar held in November 2013, under the ccordination of prefessor Marcio Serelle with the Research Group Narrative and Media, at the Pontifical Catholic University of Minas Gerais.